2013
DOI: 10.1002/ana.23882
|View full text |Cite
|
Sign up to set email alerts
|

The changing clinical course of multiple sclerosis: A matter of gray matter

Abstract: A prediction model based on age, cortical lesion load, and cerebellar cortical volume suitably explains the probability of relapsing-remitting MS patients evolving into the progressive phase. Gray matter damage appears to play a pivotal role in determining the changing clinical course of MS.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

3
79
0
4

Year Published

2015
2015
2023
2023

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 78 publications
(86 citation statements)
references
References 29 publications
(44 reference statements)
3
79
0
4
Order By: Relevance
“…Interestingly, the subpopulation of SPMS cases with higher levels of meningeal inflammation and grey matter damage were characterised clinically by a more rapidly progressive disease course 17,37,94,105 , although it should be noted that this population of patients clearly represent the more aggressive end of the spectrum of heterogeneous presentations. The link between cortical pathology and a rapidly progressive disease course has also been described in a large proportion of multiple sclerosis cases using non-conventional imaging techniques 39,105 .…”
Section: Role Of Meningeal Inflammatory Infiltratesmentioning
confidence: 99%
See 1 more Smart Citation
“…Interestingly, the subpopulation of SPMS cases with higher levels of meningeal inflammation and grey matter damage were characterised clinically by a more rapidly progressive disease course 17,37,94,105 , although it should be noted that this population of patients clearly represent the more aggressive end of the spectrum of heterogeneous presentations. The link between cortical pathology and a rapidly progressive disease course has also been described in a large proportion of multiple sclerosis cases using non-conventional imaging techniques 39,105 .…”
Section: Role Of Meningeal Inflammatory Infiltratesmentioning
confidence: 99%
“…The link between cortical pathology and a rapidly progressive disease course has also been described in a large proportion of multiple sclerosis cases using non-conventional imaging techniques 39,105 . These results support the idea that increased grey matter pathology, alone or in addition to white matter pathology, may be associated with a more rapid and aggressive disease course from early phases of the disease and that meningeal inflammation may in part be responsible for this increased pathology.…”
Section: Role Of Meningeal Inflammatory Infiltratesmentioning
confidence: 99%
“…These associations become more remarkable with disease progression from CIS to SPMS. [54][55][56][57][58][59][60][61][62][63]. Particularly worth of interest are studies that have demonstrated an association between cerebellar GM loss and the degree of disability in the cerebellar functional system of EDSS [60,64].…”
Section: Gm Atrophy and Disabilitymentioning
confidence: 99%
“…[1][2][3] In some individuals, cortical demyelination exceeds white matter demyelination, 2 and cortical lesions may be more strongly associated with disability and disability progression than white matter lesions. [4][5][6][7][8] Cortical and white matter lesions have potentially distinct origins and levels of inflammation, 3,[9][10][11][12][13] suggesting that they may have different clinical significance and response to treatment. Finally, the clinical course of MS is often not fully explained by volume and accumulation of white matter lesions, 14 making better understanding of other types of MS pathology, including cortical lesions, imperative.…”
mentioning
confidence: 99%